Saving Private Ryan - Williams, John 1932- (DreamWorks, 1999)
Captain John Miller must take his men behind enemy lines to find Private Ryan, whose three brothers have been killed in combat. Faced with impossible odds, the men question their orders. Why are eight men risking their lives to save just one? Surrounded by the brutal realities of war, each man searches for his own answer and the strength to triumph over uncertain future with honor, decency and courage
Bildformat 1.85:1 (anamorph)
Orig.: USA 1998
For specific features see interactive menu
Special features: a special message from Stephen Spielberg (3 min.); "Into the breach": Saving Private Ryan (25 min.); theatrical trailer (3 min.); re-release trailer (2 min.); cast and crew; production notes
Keywords: Film; DVD-Video